Successful Technology Licensing - Organization, World Intellectual Property (IP for Business., 2014)
This Successful Technology Licensing (STL) Manual was developed as a response to requests for a user-friendly manual aimed primarily at an audience of businesspersons, technology managers and scientists who are dealing with licensing in the course of their work. Licensing occurs in the context of various business and collaboration relations, such as mergers and acquisitions, joint ventures, research collaboration agreements, joint research and development arrangements, etc.